Placental Findings in Singleton Stillbirths: A Case-control Study. (6th February 2018) - Ananthan, Anitha; Nanavati, Ruchi; Sathe, Pragati; Balasubramanian, Haribalakrishna
Abstract: Aims: This prospective observational study compared placental lesions of stillbirth cases and live birth controls, and aimed to determine the cause of stillbirth. Methods: The study enrolled 85 stillbirths and 85 live births at the time of delivery. Results: There was significantly increased incidence of placental abruption ( p = 0.005) and gestational diabetes ( p = 0.032) in mothers with stillbirths. Histopathological examination of placenta was significantly abnormal in stillbirths compared with live births ( p = 0.004). Delayed villous maturation was significantly more in stillbirths (38.82 vs. 16.47%; p = 0.002). Acute (30.59 vs. 16.47%; p = 0.04) and chronic diffuse villitis (16.47 vs. 4.7%; p = 0.02), chorionic plate acute vasculitis (28.235 vs. 14.11%; p = 0.04) were significantly more in stillbirths. Foetal vascular thrombi in the chorionic plate (30.58 vs. 14.12%; p = 0.02) and avascular villi (24.7 vs. 8.23%; p = 0.006) were significantly more in stillbirths. Conclusion: These abnormal placental patterns could provide information about the etiopathogenisis in stillbirths of unknown aetiology.